Organization Of Training in An Educational Tool Programmed in The Subject of Technology, Theoretical Foundations of Its Improvement - Abdusalomov Okhunjan Abdusalomovich (Academia One Publishing, 2024)
this article is devoted to the correct Organization of training in technology, the orientation of students in general secondary schools to the profession in the spirit of love for the motherland, devotion to the ideas of national independence, creating conditions for their conscious and independent career choice
Keywords: technology; teaching process; Educational System; Information Communication Technology